Anti-Mycobacterium avium activity of quinolones: in vitro activities. - Klopman, G (1993)
The MICs of 88 quinolones against 14 selected reference and clinical strains of Mycobacterium avium-M. intracellular complex were determined. Agents tested included ciprofloxacin, sparfloxacin (PD 131501), and 86 other experimental quinolones. Test strains were selected to represent various susceptibilities to ciprofloxacin and other drug resistance profiles. MICs were determined by the microdilution method in 7HSF broth, with incubation for 14 days at 35 degrees C. The results showed 25 of the quinolones to be active against the strains, with MICs for 90% of the strains (MIC90s) of 2 to 32 micrograms/ml. Ten of these compounds had activities equivalent to or greater than that of ciprofloxacin. The most active compound was PD 125354, with an MIC50 of 0.5 micrograms/ml and an MIC90 of 2 micrograms/ml; comparable values for ciprofloxacin were 4 and 8 micrograms/ml, respectively. The next most active compounds, with MIC90s of 4 micrograms/ml, were sparfloxacin (PD 131501), PD 123982, PD 135144, and PD 119421. MIC90s of PD 131575, PD 126889, PD 122642, PD 139586, and PD 143289 were 8 micrograms/ml. Further evaluation of the most active agents is warranted, as is assessment of structure-activity relationships of active and inactive agents to elucidate the active portions of the compounds and to lead to the development of compounds with enhanced activity.